New imaging techniques in characterization of adrenal masses - Eman Fahim Elbahay; Sally Emad Eldeen Ahmed; Sameh Abdelaziz Zaky Hanna (Cairo : Eman Fahim Elbahay, 2012)
Finally CT and MR remain the primary imaging modalities for characterization of adrenal lesions . Recently developed techniques may offer additional information . The value of PET and PET/CT has already been proven and other new functioal imaging techniques such as diffusion weighted imaging and MR spectroscopy may play an important role in lesion characterization in the near future
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Radio-diagnosis
Issued also as CD
Keywords: characterization; CT; MR